Bodleian Library, MS. Bodl. 862 - conservation report, 2025 - Honey, A (Bodleian Library, University of Oxford, 2025)
This report describes conservation carried out between May 2019 and February 2022, funded by an anonymous donation in memory of Edward Smith (1926-2018). The binding was conserved between May 2019 and March 2020 by Andrew Honey, the velvet covering by Prof. Maria Hayward in August 2021, and a new box was made by Bridget Mitchell of Arca Preservation in February 2022.